2022
DOI: 10.5539/jsd.v16n1p53
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of ICT/e-Government on Migrant Workers' Remittance Inflows in Bangladesh: An Empirical Study

Abstract: This research article has explored and examined the effects of ICT/e-Government measures and some other significant socioeconomic factors on migrant workers’ remittance inflows in Bangladesh; Sustainable development approach is very much related to the economic growth that can be achieved by higher remittance inflows and related factors such as ICT/e-Government measures. So far, the effects of Information and Communication Technology (ICT) and e-Government measures on remittance inflows have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In fact, internet has been identified as a key enabler of financial technology (fintech) which has brought about massive transformation in financial services delivery including remittance processing (Lewan, 2018;Mamonov, 2020). In all, the findings corroborate the conclusions of prior related studies including Elmi andNgwenyama (2020), Gascon et al (2023), Ahmed and NaRanong (2023) for Somalia, Bangladeshi and El Salvador respectively.…”
Section: Findings and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In fact, internet has been identified as a key enabler of financial technology (fintech) which has brought about massive transformation in financial services delivery including remittance processing (Lewan, 2018;Mamonov, 2020). In all, the findings corroborate the conclusions of prior related studies including Elmi andNgwenyama (2020), Gascon et al (2023), Ahmed and NaRanong (2023) for Somalia, Bangladeshi and El Salvador respectively.…”
Section: Findings and Discussionsupporting
confidence: 84%
“…Studying the role of technological development in remittances transfer of Somali migrants in Canada, Elmi and Ngwenyama (2020) found that progress in technology diffusion constitutes an important explanation for growth in migrant remittances from Canada. The contribution of digital technology to rising migrants' remittances is also attested to in a recent study by Ahmed and NaRanong (2023). Based on the outcomes of the empirical strategies, the study showed that improvement in ICT plays a key role in remittances inflow in Bangladesh.…”
Section: Literature Reviewmentioning
confidence: 65%
“…Remittances were found to have significant positive contribution to the economic growth of Azerbaizan and Armenia (Azam & Khan, 2011). However, remittance money was reported as an insignificant source of capital for the economic growth of Bangladesh (Ahmed, 2010). Sutradhar (2020) studied the impact of remittances on the economic growth in Bangladesh, India, Pakistan, and Sri Lanka.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It was also argued that remittance creates moral hazard where labour market participation is reduced because of the over reliance of recipients on the income from migrant as majority of them are no longer interested in working. It also weakens international competitiveness of export due to appreciation of the exchange rate (Acosta et al, 2009;Ahmed, 2010;Alkhathlam, 2013;Kratou & Gazdar, 2015;Pradham, 2016;Xinying, Oppong, Vitenu-Sackey, 2019;Keho, 2020;.…”
Section: Introductionmentioning
confidence: 99%